A Comparative Study of Retinal Function in Rabbits after Panretinal Selective Retina Therapy versus Conventional Panretinal Photocoagulation - Young Gun Park; Seungbum Kang; Ralf Brinkmann; Young-Jung Roh (Journal of Ophthalmology)
Purpose. This study evaluates functional changes in electroretinographic findings after selective retina therapy (SRT) compared to panretinal photocoagulation (PRP) in rabbits. Methods. The right eyes of 12 Chinchilla rabbits received 200 laser treatment spots. The right eyes of six rabbits received SRT (SRT group), whereas the other six animals were treated using PRP on the right eye (PRP group). The eyes were investigated using full-field ERG 1 hour and 3 weeks after treatment. Histologic exam to assess the tissue response of lasers was performed on 3 weeks. Results. No significant changes in the mean ROD or CR b-wave amplitudes of the SRT lesions were evident, compared to baseline, 1 h after laser treatment (p=0.372 and 0.278, resp.). In addition, the OPs and 30 Hz flickers of the SRT lesions were not significantly altered (p=0.17 and 0.243, resp.). At 3 weeks, similar results were found. Comparing the two groups, the ROD b-wave amplitude was reduced in the PRP and SRT groups to 60.04±4.2% and 92.32±6.43% of baseline (p<0.001). Histologically, there was no visible photoreceptor alterations on week 3. Conclusions. SRT in rabbit eyes induced less functional loss than PRP in both rod-mediated retinal function and cone-mediated retinal function. In addition, SRT irradiated eyes had no functional loss compared to its control.